2021
DOI: 10.3389/fphys.2021.768593
|View full text |Cite
|
Sign up to set email alerts
|

Acclimations to Cold and Warm Conditions Differently Affect the Energy Metabolism of Diapausing Larvae of the European Corn Borer Ostrinia nubilalis (Hbn.)

Abstract: The European corn borer Ostrinia nubilalis is a pest species, whose fifth instar larvae gradually develop cold hardiness during diapause. The physiological changes underlying diapause progression and cold hardiness development are still insufficiently understood in insects. Here, we follow a complex of changes related to energy metabolism during cold acclimation (5°C) of diapausing larvae and compare this to warm-acclimated (22°C) and non-diapause controls. Capillary electrophoresis of nucleotides and coenzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…At the same time, low temperature can also cause ticks to produce a variety of stress reactions. These stress reactions were participated and completed by proteins, mainly including: reasonably regulating energy metabolism; maintaining regular energy supply (Sinclair, 2015); slowing cell proliferation and realizing diapause, to reduce energy loss (Popović et al, 2021); and starting cell apoptosis to eliminate seriously damaged cells (Ren et al, 2021). Some previous research on the transcriptome and metabolome of D. variabilis (Rosendale et al, 2022) and Ixodes uriae (Benjamin et al, 2021) at low temperature found that the transcription level of many mRNAs in ticks changed after low-temperature treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, low temperature can also cause ticks to produce a variety of stress reactions. These stress reactions were participated and completed by proteins, mainly including: reasonably regulating energy metabolism; maintaining regular energy supply (Sinclair, 2015); slowing cell proliferation and realizing diapause, to reduce energy loss (Popović et al, 2021); and starting cell apoptosis to eliminate seriously damaged cells (Ren et al, 2021). Some previous research on the transcriptome and metabolome of D. variabilis (Rosendale et al, 2022) and Ixodes uriae (Benjamin et al, 2021) at low temperature found that the transcription level of many mRNAs in ticks changed after low-temperature treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These stress reactions were participated and completed by proteins, mainly including: reasonably regulating energy metabolism; maintaining regular energy supply (Sinclair, 2015); slowing cell proliferation and realizing diapause, to reduce energy loss (Popović et al. , 2021); and starting cell apoptosis to eliminate seriously damaged cells (Ren et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During diapause the insect passes through a series of distinct physiological phases including induction, maintenance, termination, and postdiapause development with specific biochemical and physiological changes (Koštál, 2006; Koštál et al, 2017). Diapausing insects harvest, accumulate, and regulate certain biochemical components like fatty acids, amino acids, polyhydric alcohols, and carbohydrates (Andreadis et al, 2008; Grubor‐Lajsic et al, 1991; Heydari & Izadi, 2014; Kojić et al, 2018; Koštál et al, 2001, 2007; Mohammadzadeh et al, 2017; Popović et al, 2021; Purać et al, 2015, 2016; Stanić et al, 2004; Teets & Denlinger, 2013; Vukašinović et al, 2013, 2015, 2018). The biochemical changes that occur during diapause have important ecological and physiological implications, particularly in terms of how metabolic reserves are allocated and used to produce other necessary metabolites during distinct phases of hibernation (Koštál et al, 2007; Sadakiyo & Ishihara, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both diapause process and temperatures have been reported to affect the expression of stress‐related genes like Grx , Hsp90 , Hsc70 , and Hsp20.1 upregulated during the initiation, Trx and Hsp90 in the early phase, and all these genes (except Trx ) increased gradually throughout the diapause in cold‐acclimated larvae of O. nubilalis (Popović et al, 2015). However, relative expression of NADH dehydrogenase, coenzyme Q cytochrome c reductase, COX, ATP synthase, ADP/ATP translocase, and prohibitin 2 were found suppressed in cold‐acclimated larvae during the initial months of diapause, which gradually increased toward the termination of diapause in O. nubilalis (Popović et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Diapause consists of three major phases-pre-diapause, diapause, and post-diapause, allowing an organism to gradually adapt to the changes in the environment and ensuring its survival [24]. An organism undergoes a wide array of molecular and biochemical adaptations during these different diapause phases, such as depression of metabolism [25,26], alteration of metabolic enzyme activity [27], synthesis of specific cryoprotectants [28,29], and changes in the lipid composition of storage molecules and membranes [30][31][32], as well as changes in the expression of genes and proteins involved in stress protection and the regulation of cell cycle and programmed cell death [33][34][35][36][37][38]. The listed adaptations allow the diapausing larvae of the ECB to develop cold hardiness and successfully overwinter [23,39].…”
Section: Introductionmentioning
confidence: 99%